Pós-tratamento de lixiviado de aterro de resíduos sólidos urbanos utilizando leitos cultivados - Cecconello, Catiane Maria (2005)
The proper disposition of solid wastes generated by the public is becoming a serious social and environmental problem. Frequently, the disposal of these wastes occurs in landfills known as "lixões" in Brazil, where no especial landfilling technique is used, which results on sanitary and environmental risks. One option for dealing with this problem is the waste disposal in sanitary landfills. However, in this kind of solid waste disposal, the water movement within the landfill dissolves many substances considered pollutants. Producing leachate within the landfill. Landfill leachate contains high concentrations of organic and inorganic substances and its environmental impact can be 200 fold higher that the sewage sludge impact. For this reason, landfills leachate must be treated before it is discharged in the watercourses. In general, when the leachate is treated by conventional wastewater treatment plant (or systems) (Aerobic, anaerobic, and facultative lagoons) the content of pollutants is still above the level considered safety to avoid environmental and public health risks. One of the alternatives for the post-treatment of landfill leachate that have been used is wetlands in some developed countries is wetlands, because is considered and efficient and low maintenance and low cost technology. In Brazil, wetlands are not so much used, which many be related to the few scientific studies published so far about the usage of this alternative where regional conditions are considered. The aim of this research was evaluate the efficiency of Typha sp (taboa) and Eleocharis sp (juncus) wetlands on the pos-treatment of the landfill leachate where the solid waste collected in the Passo Fundo town, state of Rio Grande do Sul, Brazil, are disposed. The experiments were carried out in a glass house located in University of Passo Fundo, in 2005